Pengaruh Return on Asset terhadap Earning per Share pada PT Indo Tambangraya Megah Tbk - Linda Septiana (The Indonesia Capital Market Institute, 2020)
This study aims to determine the effect of Return on Assets to Earning per Share in PT Indo Tambangraya Megah, Tbk. The study uses secondary data that has been published by the Indonesia Stock Exchange. This research method uses simple linear regression analysis techniques with a case study approach. The results of this study that Return on Assets significantly influence Earning per Share.